Effect of bacteria containing bio-fertilizer on Cd-tolerance of corn and sunflower seedlings in nutrient solution - Gajdos, Éva (Acta Agraria Debreceniensis, 2009)
Bio-fertilizers promote the nutrition uptake, firstly enhance the baring and mobility of nutrients, on the other hand biofertilizers elevate nutrient uptake in direct way. Although there are a lot of questions about their application in polluted soils. The cadmium ion is easily collectable and also transportable inside plants. Thus the Cd can get into the food-chain causing public health problems. The cadmium treatment decreases the dry matter accumulation, and the intensity of photosynthesis at the experimental plants, while the treatments with bio-fertilizer increased these parameters. The cadmium accumulated in the roots, the transport to the shoots was low. We came to the conclusion, that –because of the different nutrient-uptake systemthe sunflower took up more cadmium. Using bacterium containing bio-fertilizer the toxic effect of cadmium was moderated. By our experimental results the use of Phylazonit is offered under contaminated conditions.